Creative autism children in art perspective / Nur Nadira Mohd Kassim - Mohd Kassim, Nur Nadira (Faculty of Education, 2014)
These special needs children is a special gift for parents and teachers through all the countries. There are many disorder under neurological spectrum and one of them is Autism Spectrum. Children with Autism usually have difficulties in conveying message, thought and their feeling. But there are one way they can use to convey their thought which is by art. Art is a magic tool for special needs children especially those with autism on expressing their feeling. In this qualitative study, the researcher will investigate the ways on how the Autism Spectrum children use art throughout their daily life and how they use art in conveying message. The respondent in this research are from the Autism children and the teacher that have experience for years. The data collected from observing the autistic children dealing with art and categories in art used is based on the theories used in this research. Besides that, interviews are also included in asking open- ended question to teachers that are involve with the art therapy for children with autism spectrum.